ANALYSIS OF CONTRIBUTION AND FEASIBILITY OF LOCATION-BASED SLAUGHTER GOAT BUSINESSES IN NORTH SUMATRA - Tesra Ananta; Syahbuddin; Sarim (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The research aims to analyze the contribution and feasibility of location-based beef goat businesses in North Sumatra. The research was conducted in Langkat, Deli Serdang and Serdang Bedagei districts using a survey method in 3 sub-districts which were deliberately selected based on the largest goat population. The number of samples in this research was 60 samples, 20 respondents each from each research location. The analytical methods used are income analysis, R/C ratio and Location Quotient. The results of the analysis showed that the R/C Ratio value was 2.41, indicating that it was possible to continue and develop beef goat farming in the Langkat, Deli Serdang and Serdang Bedagei areas. The contribution of beef goat livestock in North Sumatra is 36.1%, which shows that income from the beef goat business can become a main business if it is managed appropriately. It is proven that side maintenance has a significant impact on the farmer's total income. The LQ value obtained at 2.60 is quite high, indicating that the population and availability of beef goats in North Sumatra, apart from being able to meet regional needs, can also provide opportunities for export based on business location.